Breakdowns' Diagnosis of A New Character Three-Phase High Voltage Power Supply for Industrial Microwave Generators with N=2 Magnetrons per Phase - R. Batit; M. Chraygane; M. Ferfra; M. Fadel; A. Dsoul; B. Bahani (Institute of Advanced Engineering and Science, 2016)
This paper treats the modelisation of a new three phase character high voltage supply (HV) for industrial microwave generators with N=2 magnetrons per phase. This alimentation is based on the presentation of an equivalent p circuit model of a newly dimensioned high voltage transformer. Each phase of the three phase system supplies two parallel cell voltage doublers and current stabilizer. Each of these cells in turn supplies one magnetron 800Watts / 2.45GHz. This power supply is a star connection of three identical models of the single-phase power for N=2 magnetrons. The simulation under EMTP (Electro Magnetic Transients Program) in nominal conditions allows concluding that theoretical results are adjacent to the experimental measurements. Furthermore, a failure study of six magnetron of the microwave generator is also processed. The results permit to observe that the interaction between magnetrons dosn’t influence the nominal operation of the system.